Haemolytic anaemia in Kavaratti island, Lakshadweep: A hospital based study. - Khambra, Poonam; Yadav, Amit Kumar; Salih, Anwar (Annals of Pathology and Laboratory Medicine, 2018)
Background: Anaemia is a major public health problem in developing countries like India. Kavaratti island, Lakshadweep is a remote island located in Arabian sea. There is extreme paucity of data on the type of anaemia here. Objective of this study is to take an in depth look at the various etiologies of anaemia at Kavaratti island, Lakshadweep. Methods: A total of 4526 patients were studied. Data from the anaemic individuals was collected and analyzed. The study group was subsequently divided into smaller subgroups on the basis of age and sex for analysis. The aetiology of anaemia in these cases was further investigated. Result: The prevalence of anaemia in adult males was 21.5% and in females 37%. In pregnant females anaemia was still more common (47.5%). Among children 24.6% were anaemic with female children showing higher percentage (27.4%) than males (22.9%). Anaemia was quite common in the elderly and even higher in elderly females (43%). However, the most significant finding was the high prevalence of haemolytic anaemias especially sickle cell anaemia. Conclusion: Anaemia is not a major public health problem in Kavaratti island, Lakshadweep. However, there is high prevalence of haemolytic anaemias especially sickle cell anaemia. Nutritional anaemia is quite rare. This fact may have major implications for health policy makers. DOI:10.21276/APALM.1673